2023
DOI: 10.1590/s1983-41952023000400008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the explosion of gas tanks using computational fluid dynamics

Abstract: Buildings are composed of several systems, each with specific designs and regulations to ensure that constructions are safe and viable. Many residential, commercial, and industrial buildings have systems with gas central storage, which must be subjected to strict safety criteria to avoid accidents. In addition to the safety mechanisms provided by manufacturers, designers of these gas central storage must consider other devices to reduce explosion risk and mitigate the damaging blast effects. Explosions are phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In an overpressure analysis, the portion of energy not carried by the shock wave can be called energy loss. In the study presented by Moura et al [31], this loss was estimated at approximately 25%. With this energy loss value, the TNT equivalent mass was estimated and modelled with spherical shape for a more uniform detonation energy distribution.…”
Section: Validation and Energy Lossmentioning
confidence: 88%
See 1 more Smart Citation
“…In an overpressure analysis, the portion of energy not carried by the shock wave can be called energy loss. In the study presented by Moura et al [31], this loss was estimated at approximately 25%. With this energy loss value, the TNT equivalent mass was estimated and modelled with spherical shape for a more uniform detonation energy distribution.…”
Section: Validation and Energy Lossmentioning
confidence: 88%
“…The main numerical validation process in this work was the same presented by Moura et al [31]. These researchers compared the overpressure peaks from the domestic gas tank explosion obtained by numerical simulations with the results of the equations listed in Table 1 and with experimental data from Tschirschwitz et al [8], as shown in Figure 4.…”
Section: Validation and Energy Lossmentioning
confidence: 99%